Efficacy and safety of hydroxychloroquine when added to stable insulin therapy in combination with metformin and glimepiride in patients with type 2 diabetes compare to sitagliptin - Kumar, Vijay; Singh, M. P.; Singh, Amrendra Prasad; Pandey, Mani Shankar; Kumar, Suraj; Kumar, Sumit (International Journal of Basic & Clinical Pharmacology, 2018)
Background: The trial was done to evaluate the efficacy and tolerability of hydroxychloroquine when added to stable insulin therapy in combination with metformin and glimepiride in patients with type 2 diabetes (T2DM) compare to sitagliptin. Methods: After two weeks run in period, eligible patients inadequately controlled on long acting, intermediate acting or premixed insulin (HbA1c ≥7.5% and ≤10%), in combination with metformin and glimepiride were randomised 1:1 to the addition of once daily hydroxychloroquine 400mg or sitagliptin 100mg over 24weeks study period. The primary endpoint was HbA1c change from baseline at week 24. Home based glucometer was used to determine finger stick glucose value to detect hypo or hyperglycemia periodically. Results: At 24 weeks, the addition of hydroxychloroquine significantly (p <0.001) reduced HbA1c by 1.3% compared with Sitagliptin which was 0.9%. A greater proportion of patients achieved an HbA1c level <7% while randomised to Hydroxychloroquine as compared with sitagliptin (31 vs. 18% respectively; p <0.001). The addition of hydroxychloroquine significantly (p<0.001) reduced fasting plasma glucose by 31.0mg/dl (vs 23.2mg/dl with sitagliptin) and post prandial plasma glucose by 52.1mg/dl (vs 41mg/dl with sitagliptin) relative to sitagliptin. The difference in mean value of total daily insulin dose showed a highly significant decrease (P <0.0001) from baseline to end of the treatment with hydroxychloroquine i.e. from 41±10.2 to 31.87±16.49 IU as compare to sitagliptin i.e. from 41±10.6 to 37.91±11.71 IU. And also highly significant (P <0.0001) decrease in mean weight was observed at the end of trial with hydroxychloroquine. Conclusions: Hydroxychloroquine decreases HbA1c in patients whose type 2 diabetes is poorly controlled with stable-dose insulin therapy with metformin and glimepiride.